2022
DOI: 10.1002/smtd.202270047
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the Deep Spinal Cord Microvascular Structure and Function with High‐Speed NIR‐II Fluorescence Microscopy (Small Methods 8/2022)

Abstract: In article number 2200155, Yan, Qian, Xi, and co-workers obtained the deep spinal cord (SC) vascular structure and achieved fast monitoring of indocyanine-green-labeled red blood cells up to 100 fps by NIR-II fluorescent microscopy, which exhibits the great potential of NIR-II window on SC imaging. The imaging research on SC vasculature is crucial, yet the high scattering tissue greatly affects the improvement of microscopic imaging depth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Previous studies reported a kind of aggregation-induced emission (AIE) luminogen named DCBT with a large multi-photon absorption cross-section, which could be utilized for cortical microvasculature imaging on mice and even non-human primates. [26,51,52] Using DCBT nanoparticles (NPs) as the 2PF probes, cerebral vascular images of mice were obtained as the ground truth (Figure S1, Supporting Information). In order to acquire the NIR-II fluorescence microscopic images of cerebral blood vessels as the input of the SRN, the PEGylated PbS/CdS quantum dots (QDs) emitting at ≈1600 nm were developed, whose high fluorescence intensity and stability would facilitate long-term imaging in vivo (Figure S1, Supporting Information).…”
Section: Training the Srn For The High Optical Throughput Nir-ii Fluo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported a kind of aggregation-induced emission (AIE) luminogen named DCBT with a large multi-photon absorption cross-section, which could be utilized for cortical microvasculature imaging on mice and even non-human primates. [26,51,52] Using DCBT nanoparticles (NPs) as the 2PF probes, cerebral vascular images of mice were obtained as the ground truth (Figure S1, Supporting Information). In order to acquire the NIR-II fluorescence microscopic images of cerebral blood vessels as the input of the SRN, the PEGylated PbS/CdS quantum dots (QDs) emitting at ≈1600 nm were developed, whose high fluorescence intensity and stability would facilitate long-term imaging in vivo (Figure S1, Supporting Information).…”
Section: Training the Srn For The High Optical Throughput Nir-ii Fluo...mentioning
confidence: 99%
“…[25] Because of the excellent penetration depth, high temporal resolution, and low phototoxicity, NIR-II fluorescence wide-field microscope has been widely utilized as an intravital microscopic technology. [26][27][28][29][30][31] So far, a 1.4 mm imaging depth for cerebral vessels of mice has been reported. [25] However, the spatial resolution of NIR-II fluorescence wide-field microscope remains unsatisfactory, predominantly due to image degradation attributable to biological tissue and optical systems, with the former being of particular concern.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by its capacity to deliver high spatiotemporal resolution, contactless operation, and radiation-free imaging, distinguishing it from computed tomography (CT), ultrasound, and positron emission computed tomography (PET) [2,3]. Wherein, intravital optical microscopic imaging with substantial imaging depth holds a pivotal role in comprehending biological structure and function, while also contributing to clinical diagnosis and treatment [4][5][6][7]. The primary factor limiting spatial resolution, signal-to-background ratio (SBR), and imaging depth is the scattering effect within biological tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the emergence of three-photon fluorescence imaging technology has further extended high-spatial resolution brain imaging capabilities to depths exceeding 2 mm [19]. Multi-photon fluorescence microscopy has been primarily advanced within the domain of neuroscience, with its applicability gradually extending to various other fields [5,6,[20][21][22]. However, given the varying optical properties of biological tissues, the choice of multi-photon fluorescence imaging windows should be tailored to specific application scenarios.…”
Section: Introductionmentioning
confidence: 99%